Activation of Adhesion GPCR EMR2/ADGRE2 Induces Macrophage Differentiation and Inflammatory Responses via Gα16/Akt/MAPK/NF-κB Signaling Pathways - I, Kuan-Yu; Huang, Yi-Shu; Hu, Ching-Hsun; Tseng, Wen-Yi; Cheng, Chia-Hsin; Stacey, Martin; Gordon, Siamon; Chang, Gin-Wen; Lin, Hsi-Hsien (Frontiers in Immunology, 2017)
EMR2/ADGRE2 is a human myeloid-restricted adhesion G protein-coupled receptor critically implicated in vibratory urticaria, a rare type of allergy caused by vibration-induced mast cell activation. In addition, EMR2 is also highly expressed by monocyte/macrophages and has been linked to neutrophil migration and activation. Despite these findings, little is known of EMR2-mediated signaling and its role in myeloid biology. In this report, we show that activation of EMR2 via a receptor-specific monoclonal antibody promotes the differentiation of human THP-1 monocytic cell line and induces the expression of pro-inflammatory mediators including IL-8, TNF-α, and MMP-9. Using specific signaling inhibitors and siRNA knockdowns, biochemical and functional analyses reveal that the EMR2-mediated signaling is initiated by Gα16, followed by the subsequent activation of Akt, ERK, JNK and NF-κB. Our results demonstrate a functional role for EMR2 in the differentiation and inflammatory activation of human monocytic cells and provide potential targets for myeloid cell-mediated inflammatory disorders.